Average Max Round Robin Algorithm: A Case Study - Putra, Tri Dharma; Purnomo, Rakhmat (Politeknik Ganesha Medan, 2023)
Round Robin Algorithm is one wellknown algorithm in real time system. Several variants of round robin algorithms are in the fields. Average max round robin algorithm is a breakthrough to optimize context switching or also called quantum. Context switching is one big problem in round robin algorithm. To optimize high context switching is the key solution. This will make this algorithm efficient. There should be a way to optimize this context switching. Then the average max round robin algorithm is one solution to this problem. The average max algorithm is defined by finding the average of burst time then add the maximum burst time to the average burst time. Then calculate again the average of the two. The calculation will be iterated in the next round robin cycle. Here, in this journal, three case studies are discussed. Each with different burst times to understand this average max round robin algorithm more clearly. In the first case study we get turn around time 34 ms, and average waiting time 20.6 ms. In the second case study, we get average turn around time 21.8 ms, and the average waiting time 13 ms. And in the last case study, the third one, we get turn around time 12.2 ms, and the average waiting time 6.6 ms. There is no calculation for the second iteration for all case studies. Since the left burst time is only in one process. Optimizing the context switching, minimizing average turnaround time, and average waiting time is the key solution to round robin algorithm.